TRANSLATIONS OF THREE WORKS RELATED TO THE PEACH BLOSSOM SPRING (BULLETIN OF TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV. ORIENTAL LANGUAGES AND LITERATURES, 2025)
This publication offers Ukrainian translations of three Chinese literary works united by the motif of the Peach Blossom Spring: "The Tale of the Peach Blossom Spring" by Tao Yuanming (~365–427), the poem "The Peach Blossom Journey" by Wang Wei (693/694/701–761), and an excerpt from the play "Secret Love in Peach Blossom Land" by Taiwanese director and playwright Lai Shengchuan (b. 1954).Tao Yuanming’s work had previously been translated into Ukrainian and published in 2010 in the Anthology of Chinese Literature (3rd–6th centuries), compiled by Ya. V. Shekera. The works by Wang Wei and Lai Shengchuan are presented in Ukrainian translation for the first time.
Keywords: TRANSLATIONS OF THREE WORKS RELATED TO THE PEACH BLOSSOM SPRING